Implementation of the Principle of Proportionality in Criminal Sentencing in Indonesia - Axl Mattew Situmorang; I Gede Agus Kurniawan; I Made Wirya Darma (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to analyze the normative implementation of the principle of proportionality in the imposition of criminal penalties in Indonesia. The principle of proportionality is a fundamental concept in criminal law that requires the punishment imposed to be balanced and commensurate with the degree of fault and the impact of the criminal act committed. This research employs a normative juridical method with statute approach, conceptual approach, and legal doctrine approach. Data were collected through literature studies of relevant legislation, legal doctrines, and court decisions. The findings indicate that although the principle of proportionality has been regulated in various Indonesian laws and regulations, its application in criminal justice practice still faces several obstacles, such as judicial subjectivity and inconsistency in sentencing. Furthermore, cases have been found where the penalties imposed are disproportionate to the offender’s level of fault, potentially resulting in injustice. Therefore, this study recommends strengthening guidelines for applying the principle of proportionality within the criminal justice system, including training for law enforcement officers and the development of clearer and more measurable sentencing standards. It is expected that this research will contribute to the advancement of a more just and civilized criminal law system in Indonesia through the consistent and appropriate application of the principle of proportionality.